Assessment of Phytochemical Properties of Nigella sativa Seeds Essential Oil and Its Potential Antimicrobial Activity against Staphylococcus aureus in the Context of Safety Profiles and Therapeutic Applications in Neurosurgical Interventions - Farag, Noha Elsayed Hassan; Ahmedani, Elsamoual Ibrahim; Sheriff, Maqbul Muazzam; Alsubaie, Abeer Saad; Alkhamis, Zainab Anwar; Almatari, Shroq Saleh; Alsobhi, Lama Abdulrhim; Alrefai, Amani Khaled; Saeed, Eman Esamuddin; Abdalla, Logen Osman; Alharbi, Bushra Salman; Obaid, Abdulrahman Adel Abdulrahman; et al. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This comprehensive study explored the phytochemical properties of Nigella sativa L (N. sativa L) seeds essential oil using gas chromatography-mass spectrometry (GC-MS) analysis, with a specific focus on its potential compound Thymoquinone (TQ) exhibiting antimicrobial activity against Staphylococcus aureus (S. aureus) in the context of neurosurgical interventions.The study employs a meticulous methodology, encompassing the preparation of N. sativa essential oil, qualitative phytochemical screening, quantitative GC-MS analysis, and the antimicrobial analysis, employing Disc Diffusion, Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC) evaluations to demonstrate the substantial inhibitory and bactericidal effects against Staphylococcus aureus (S.aureus}. comprehensive assessment of antimicrobial activity.The qualitative analysis reveals the presence of alkaloids, flavonoids, phenols, tannins, cardiac glycosides, steroids, saponins, and terpenoids, underscoring the multifaceted pharmacological potential of the essential oil. The quantitative GC-MS analysis provides a detailed breakdown of the chemical composition under different extraction conditions, showcasing the complexity of N. sativa essential oil. The study thoroughly compares the antimicrobial efficacy of N. sativa essential oil with various antibiotics, employing Disc Diffusion, MIC, and MBC analyses. N. sativa demonstrates substantial inhibitory effects, with a 29 mm zone comparable to Gentamycin. The MIC and MBC values align with established antibiotics, indicating similar bacteriostatic and bactericidal properties. Despite slightly lower potency than Vancomycin and Methicillin, N. sativa exhibits considerable antimicrobial effectiveness. This study contributes valuable insights into the phytochemical composition of N. sativa seeds essential oil and its potential as an antimicrobial agent in the context of neurosurgical interventions paves the way for future research.